Functionally sequenced scanpath similarity method (FuncSim): Comparing and evaluating scanpath similarity based on a task’s inherent sequence of functional (action) units - Rebecca M. Foerster; Werner X. Schneider (Journal of Eye Movement Research)
Measures of scanpath similarity are essential in many domains of eye tracking research. Depending on the question, different calculations are adequate. We (Foerster, Carbone, Koesling, & Schneider, 2011) developed a method with a functional matching procedure suitable for sequential tasks. Here, we report two extensions. We introduced an alignment variant making the method more robust across tasks. We added the possibility to compare scanpaths according to multiple characteristics. The extended method, here called “functionally sequenced scanpath similarity method (FuncSim)” reveals whether gaze characteristics are similar in the same functional units of a task, opposed to when participants are engaged in different functional units. Finally, the advantages of our method are presented and compared to other methods of scanpath similarity calculation.